Dioscorea spp. (A Wild Edible Tuber): A Study on Its Ethnopharmacological Potential and Traditional Use by the Local People of Similipal Biosphere Reserve, India - Kumar, Sanjeet; Das, Gitishree; Shin, Han-Seung; Patra, Jayanta Kumar (Frontiers in Pharmacology, 2017)
A number of wild crops remain unexplored in this world and among them some have excellent medicinal and nutritional properties. India is a harbor of biodiversity in general and phytodiversity in particular. The plant diversity is distributed from the Western Ghats to Eastern Ghats, along with the North-Eastern region and from the Greater Himalayas to the plain of Ganga. Among these distributed floral regions of the country, the Eastern Ghats are important due to their rich floral diversity. The forests of Odisha form a major part of Eastern Ghats in general and the Similipal Biosphere Reserve (SBR) in particular. The SBR is inhabited by many tribal communities. The food and medicinal habits of these communities are not fully explored even today. They are dependent on the forests of SBR for their food and medicine. Among their collections from forests, root and tuberous plants play a significant role. The tribal communities of SBR use about 89 types of tuberous plants for various purposes. Dioscorea is one such tuber, having maximum use among the tribal of SBR. However, less documentation and no specific reports are available on the food and medicinal values of the species available in this part of the World. Dioscorea species, popularly known as Yam worldwide and as Ban Aalu in Odisha, India, is a prime staple medicinal-food substitute for the majority of rural and tribal people of the state of India. Of the 13 Dioscorea species available in SBR, 10 species are known to be bitter in taste and unpalatable when taken raw. Since less documentation is available on the Dioscorea species of SBR and their traditional uses, the present study was focused on the ethnobotany, nutritional and pharmacological values of these species along its nutraceutical importance.